(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2018)
This work is about how secondary school students know and understand the matter of the last dictatorship in Argentina, a main subject in regard to their education as democratic citizens. For this purpose, quantitative data resulting from a completed research on the Mercosur countries are used and compared with those obtained through the narratives of 5th year students of a qualitative project still ongoing and focused on the city of La Plata (capital of Buenos Aires province).